FAILURE OF CORPORATE GOVERNANCE - A CASE STUDY AT PT GARUDA INDONESIA TBK - Yuniarwati; I Cenik Ardana; Elizabeth Sugiarto Dermawan (Jurnal Akuntansi, 2021)
The topic of corporate governance became the focus of research, discussions, seminars and recent regulatory reforms following a wave of failures in implementing the governance of multinational companies in various countries. In Indonesia, PT Garuda Indonesia Tbk is a public company that has failed in implementing a good corporate governance system. The purpose of this study is to investigate the factors causing the failure of corporate governance. The research method uses a single case study. The research subject was PT Garuda Indonesia Tbk during the period 2018-2019. The results showed that the failure of the implementation of the corporate governance system at PT Garuda Indonesia Tbk was caused by the crisis of ethical leadership in almost all the highest ranks of the company. This study reinforces the findings of the latest researchers who revealed the absence of ethical leadership as a cause of failure in implementing corporate governance in various companies and emphasized the important role of ethical leadership in a business entity or organization.   Keywords: ethical leadership, corporate governance, case studies